Zerumbone Protects against Carbon Tetrachloride (CCl4)-Induced Acute Liver Injury in Mice via Inhibiting Oxidative Stress and the Inflammatory Response: Involving the TLR4/NF-κB/COX-2 Pathway - Meilin Wang; Jingling Niu; Lina Ou; Bo Deng; Yingyi Wang; Sanqiang Li (Molecules, 2019)
The natural compound Zerumbone (hereinafter referred to as ZER), a monocyclic sesquiterpenoid, has been reported to possess many pharmacological properties, including antioxidant and anti-inflammatory properties. This study aimed to investigate the underlying mechanism of ZER against acute liver injury (ALI) in CCl4-induced mice models. ICR mice were pretreated intraperitoneally with ZER for five days, then received a CCl4 injection two hours after the last ZER administration and were sacrificed 24 h later. Examination of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities and the histopathological analysis confirmed the hepatoprotective effect of ZER. Biochemical assays revealed that ZER pretreatment recovered the activities of antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), restored the glutathione (GSH) reservoir, and reduced the production of malondialdehyde (MDA), all in a dose-dependent manner. Furthermore, administration of ZER in vivo reduced the release amounts of pro-inflammatory cytokines interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) and inhibited the increased protein levels of Toll-like receptor 4 (TLR4), nuclear factor-kappaB (NF-κB) p-p65, and cyclooxygenase (COX-2). Further studies in lipopolysaccharide (LPS)-induced Raw264.7 inflammatory cellular models verified that ZER could inhibit inflammation via inactivating the TLR4/NF-κB/COX-2 pathway. Thus, our study indicated that ZER exhibited a hepatoprotective effect against ALI through its antioxidant and anti-inflammatory activities and the possible mechanism might be mediated by the TLR4/NF-κB/COX-2 pathway. Collectively, our studies indicate ZER could be a potential candidate for chemical liver injury treatment.